2019
DOI: 10.4067/s0718-58392019000400586
|View full text |Cite
|
Sign up to set email alerts
|

Sesame production and composition compared with conventional forages

Abstract: Sesamum indicum L. has the potential to be cultivated as a forage plant in hot and dry climate regions, and it can be used to increase the food security of a herd. The objective of this study was to evaluate growth, production, and chemical composition of S. indicum compared with conventional forages used for silage production. The experiment used a randomized complete block design with split-plots related to time and four replicates per treatment. The plots consisted of four treatments (Zea mays L., Helianthu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 18 publications
0
4
0
2
Order By: Relevance
“…Fiber is present in the cell wall of vegetables, formed primarily by cellulose, hemicellulose, lignin, protein, and other compounds. It has a priority function in ruminant nutrition, as a source of energy and to stimulate the fermentation processes [ 48 , 49 , 50 ]. The fiber digestion of forage is not constant for all animals or for all feeding conditions, varying from 135 to 780 g/kg in DM basis, but the main variation is due to differences in the structure, chemical composition, and maturity.…”
Section: Discussionmentioning
confidence: 99%
“…Fiber is present in the cell wall of vegetables, formed primarily by cellulose, hemicellulose, lignin, protein, and other compounds. It has a priority function in ruminant nutrition, as a source of energy and to stimulate the fermentation processes [ 48 , 49 , 50 ]. The fiber digestion of forage is not constant for all animals or for all feeding conditions, varying from 135 to 780 g/kg in DM basis, but the main variation is due to differences in the structure, chemical composition, and maturity.…”
Section: Discussionmentioning
confidence: 99%
“…The chemical composition in forage is related to forage quality and degradation ( 30 ). In this study, the removal of hemicellulose from the cellulose–hemicellulose–lignin structure led to a reduction in NDF and ADF contents in rice straw treated with LAB and LAB + M. Notably, the low NDF and ADF were associated with higher feed quality and degradation, as well as higher dry matter intake ( 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…Abbasi et al (2018) reported that harvested amaranth forage contained 233 g/kg dry matter with 18.7% crude protein, 42.0 %NDFom, 27.5 %ADFom, 4.46 %ADL, 5.7 %EE, 6.25 %WSC, 14.5 %ash, 1.11% Ca, 0.66 % P and 8. 4 Phytomass is an important source for renewable energy production. The production of biomethane gas via anaerobic digestion using lignocellulosic phytomass as a renewable energy source is both sustainable and environmentally friendly.…”
Section: Physico-mechanical Properties Of Seedsmentioning
confidence: 99%
“…The analysis of the situation in the given field of research demonstrates that it is possible, under the soilclimatic conditions of the Republic of Moldova, to make full use of the potential of a number of non-traditional plants from the families Amaranthaceae, Brassicaceae, Linaceae, Pedaliaceae, Polygonaceae, which are studied to a lesser extent by the international scientific community (Abbasi et al, 2018; Alekksha Kudos, Chandan, 2018;Amorim et al, 2019;Biel et al, 2017;Bhat et al, 2018;Das, 2016;Elleuch et al, 2007;Gautam et al, 2016;Herrmann et al, 2016;Kshnikatkina et al, 2005;Kukusheva and Stepanov, 2016;Mursec et al, 2009;Peiretti, 2018;Póti et al, 2014;Rahnama, Safaeie, 2017;Rakhmetov, 2011Rakhmetov, , 2018Rakhmetov and Rakhmetova, 2006;2011;Rakhmetov et al, 2004;Seppälä, 2013;Słomka and Wójcik Oliveira, 2021;Ustak et al, 2011;Uteush, 1990;Von Cossel, 2019) and the one from the Republic of Moldova (Chisnicean et al, 2011;Teleuţă and Ţîţei, 2016;Teleuță et al, 2008;Țîței, 2015, 2020Țîței and Roșca, 2021;Teleuţă and Ţîţei, 2016).…”
Section: Introductionmentioning
confidence: 99%